Medicinal product and dietary supplement as waste - legal issues - Justyna Rogowska; Agnieszka Zimmermann (Polish Pharmaceutical Society, 2023)
The issue of waste is a topic widely discussed at both European and national levels. The insufficient share of separately collected waste in the stream and the too large amount of waste sent to landfills, combined with the need for Poland to implement the concept of a circular economy, makes it necessary to analyze the possibility of making changes, primarily in the legal area. Their goal should be to minimize the amount of waste generated and to more effectively counteract the threats resulting from the presence of waste in the environment. Waste of a special nature are medicinal products generated both in pharmacies and households. Improper handling of unnecessary/expired medicinal products may cause negative effects on both the environment and human health. This problem also applies to dietary supplements, which are treated as food products under the law, even though they may contain compounds that may have a negative impact on health and on the environment. Proper handling of waste from medicinal products and dietary supplements depends on the correct classification of these types of waste. The aim of the work is to analyze the regulations regarding the classification of waste from medicinal products (both generated in pharmacies and households) and dietary supplements, as well as legal problems related to this classification. First of all, the classification of waste resulting from dietary supplements is controversial. This is important because correct categorization determines the appropriate, safe method of waste disposal (thermal transformation, storage in landfills). The work also points to problems in defining concepts at the intersection of environmental protection regulations and regulations relating to medicinal products. The analysis was limited to waste from medicinal products and dietary supplements generated in pharmacies and households and does not apply to waste from pharmaceutical plants and chemicals used in pharmacies to produce prescription and pharmaceutical drugs.